2021
DOI: 10.3389/fmicb.2021.738780
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Extracellular Proteins in Acinetobacter baumannii in Sessile Mode of Growth

Abstract: Acinetobacter baumannii is a problematic nosocomial pathogen owing to its increasing resistance to antibiotics and its great ability to survive in the hospital environment, which is linked to its capacity to form biofilms. Structural and functional investigations of post-translational modifications, such as phosphorylations, may lead to identification of candidates for therapeutic targets against this pathogen. Here, we present the first S/T/Y phosphosecretome of two A. baumannii strains, the reference strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…Thus, Massier, et al [33] reported significant differences in the phosphorylation rates of extracellular proteins in planktonic and sessile Acinetobacter baumannii cells. These authors also demonstrated that some phosphosites were located in key regions of proteins involved in antibiotic resistance, such as in betalactamases [33].…”
Section: An Alteration Of the Cellular Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, Massier, et al [33] reported significant differences in the phosphorylation rates of extracellular proteins in planktonic and sessile Acinetobacter baumannii cells. These authors also demonstrated that some phosphosites were located in key regions of proteins involved in antibiotic resistance, such as in betalactamases [33].…”
Section: An Alteration Of the Cellular Metabolismmentioning
confidence: 99%
“…Low penetration of the antimicrobial Decrease of the local concentration of the antimicrobial [15,16] Low growth rate Decrease of the efficacy of some antimicrobials (dormancy) [19][20][21] Metabolism alterations Accumulation of proteins involved in adaptation, target modifications [25,26] Oxygen gradient Decrease of the efficacy of some antimicrobials (intracellular penetration, dormancy) [33][34][35] Presence of persisters Decrease of the efficacy of some antimicrobials (dormancy) [37][38] Quorum sensing Activation of efflux pumps [43] Stress responses Cross-resistance against antimicrobials [50] A Diffusional Resistance to Inhibitors…”
Section: Mechanism Involved Effect Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…baumannii resistance. , Recently, the phospho-secretomes of two A. baumannii strains, the reference strain ATCC 17978 and the virulent multidrug resistant strain AB0057, highlighted a higher number of phosphoproteins in the biofilm mode of growth compared to the planktonic growth . Moreover, five phosphosites were detected on the T6SS tube protein Hcp .…”
Section: Introductionmentioning
confidence: 99%
“…baumannii strains, the reference strain ATCC 17978 and the virulent multidrug resistant strain AB0057, highlighted a higher number of phosphoproteins in the biofilm mode of growth compared to the planktonic growth . Moreover, five phosphosites were detected on the T6SS tube protein Hcp . After mutagenesis, specific phosphorylated residues were clearly shown to be required for Hcp secretion and therefore T6SS activity.…”
Section: Introductionmentioning
confidence: 99%